Validation and analysis of MOPITT CO observations of the Amazon Basin - M. N. Deeter; S. Martínez-Alonso; L. V. Gatti; M. Gloor; J. B. Miller; L. G. Domingues; C. S. C. Correia (Atmospheric Measurement Techniques, 2016)
We analyze satellite retrievals of carbon monoxide from the MOPITT (Measurements of Pollution in the Troposphere) instrument over the Amazon Basin, focusing on the MOPITT Version 6 "multispectral" retrieval product (exploiting both thermal-infrared and near-infrared channels). Validation results based on in situ vertical profiles measured between 2010 and 2013 are presented for four sites in the Amazon Basin. Results indicate a significant negative bias in retrieved lower-tropospheric CO concentrations. The possible influence of smoke aerosol as a source of retrieval bias is investigated using collocated Aerosol Robotic Network (AERONET) aerosol optical depth (AOD) measurements at two sites but does not appear to be significant. Finally, we exploit the MOPITT record to analyze both the mean annual cycle and the interannual variability of CO over the Amazon Basin since 2002.